Endothelial Myocyte Enhancer Factor 2c Inhibits Migration of Smooth Muscle Cells Through Fenestrations in the Internal Elastic Lamina. Issue 7 (July 2017) - Lu, Yao Wei; Lowery, Anthony M.; Sun, Li-Yan; Singer, Harold A.; Dai, Guohao; Adam, Alejandro P.; Vincent, Peter A.; Schwarz, John J.
Abstract : Objective—: Laminar flow activates myocyte enhancer factor 2 (MEF2) transcription factors in vitro to induce expression of atheroprotective genes in the endothelium. Here we sought to establish the role of Mef2c in the vascular endothelium in vivo. Approach and Results—: To study endothelial Mef2c, we generated endothelial-specific deletion of Mef2c using Tie2-Cre or Cdh5-Cre-ER T2 and examined aortas and carotid arteries by en face immunofluorescence. We observed enhanced actin stress fiber formation in the Mef2c-deleted thoracic aortic endothelium (laminar flow region), similar to those observed in normal aortic inner curvature (disturbed flow region). Furthermore, Mef2c deletion resulted in the de novo formation of subendothelial intimal cells expressing markers of differentiated smooth muscle in the thoracic aortas and carotids. Lineage tracing showed that these cells were not of endothelial origin. To define early events in intimal development, we induced endothelial deletion of Mef2c and examined aortas at 4 and 12 weeks postinduction. The number of intimal cell clusters increased from 4 to 12 weeks, but the number of cells within a cluster peaked at 2 cells in both cases, suggesting ongoing migration but minimal proliferation. Moreover, we identified cells extending from the media through fenestrations in the internal elastic lamina into the intima, indicating transfenestral smooth muscle migration. Similar transfenestral migration was observed in wild-type carotid arteries ligated to induce neointimal formation. Conclusions—: These results indicate that endothelial Mef2c regulates the endothelial actin cytoskeleton and inhibits smooth muscle cell migration into the intima. Abstract : Supplemental Digital Content is available in the text.